Analysis for models of interaction between road passenger transport operators - I. I. Lyubimov; N. N. Yakunin; N. V. Yakunina (Вестник СибАДИ, 2023)
Introduction. The authors consider the current models for the organization of urban passenger road transport, the structure of each of the models and their characteristics. The reason for writing the work was the poor study of the factors that determine the break-even transportation of passengers and, as a result, the construction on this basis of a system of interaction between transport authorities and transport operators. Thus, the purpose of the study is to create models of interaction between subjects and objects of passenger road transport. The working hypothesis of the study is to overcome the existing fragmentation of models through the development of additional blocks, the content of which is a scientifically based choice of models for the interaction of participants in the transport process in the system of passenger road transportation.Methods and materials. Three existing models for organising the work of passenger road transport are analysed. Their influence on the economic efficiency and safety of the transport process is considered. The prerequisites for the creation of algorithms for the transition from one model to another and for evaluating their effectiveness are determined.Results. According to the authors, this study will be useful for both the organizers of passenger road transport and carriers. From a practical point of view, this study will be useful to improve the efficiency and break-even of passenger road transport, as well as to maximize the ‘transparency’ of financial interaction between participants in this market.Conclusions. Further direction of research on this topic will be carried out in the direction of developing a methodology for switching models between themselves, i.e. when and how it is expedient to apply one or another model of passenger road transportation.